Mandarin fish tankyrase 1-like protein regulates the Wnt/β-catenin pathway and facilitates the infectious spleen and kidney necrosis virus replication - Zhimin Li; Yashan Wu; Jian He; Kun Wu; Shaoping Weng; Changjun Guo; Jianguo He (Comparative Immunology Reports)
Tankyrase (TNKS), a poly (ADP-ribose) polymerase (PARP) protein, mediates the PARylation of substrates, ultimately guiding them towards proteasome-dependent degradation or altering their localization. Recent studies suggest that TNKS may play a crucial role in both innate immunity and viral infection, yet its function in teleost fish remains unexplored. This study aimed to investigate the roles of mandarin fish (Siniperca chuatsi) TNKS1-like (scTNKS1-like) in the Wnt/β-catenin signaling pathway and its impact on infectious spleen and kidney necrosis virus (ISKNV) infection. Bioinformation analysis results showed that scTNKS1-like contained ANK, SAM, and PARP domains, with its sequence highly conserved across different species. Expression pattern analysis showed that scTNKS1-like mRNA was ubiquitously distributed in all tissues and was significantly upregulated in response to immune stimuli and ISKNV infection. Dual-luciferase reporter assays indicated that scTNKS1-like could evoke and positively regulate the Wnt/β-catenin signaling pathway. Protein degradation assays and co–immunoprecipitation experiment further showed that scTNKS1-like interacted with and regulated axis inhibitory protein 1 to activate the Wnt/β-catenin signaling pathway. Moreover, it was found that scβ-catenin activated the Wnt/β-catenin signaling pathway, which in turn enhanced ISKNV replication. Furthermore, scTNKS1-like was observed to significantly upregulate ISKNV replication. These findings demonstrated the role of scTNKS1-like in teleost fish and contribute to our understanding of its function in virus infection.